1996
DOI: 10.1017/s0022112096008336
|View full text |Cite
|
Sign up to set email alerts
|

On the formation of longitudinal vortices in a turbulent boundary layer over wavy terrain

Abstract: Parallel inviscid O(1) shear interacting with O(ε) spanwise-independent neutral rotational Rayleigh waves are used to model turbulent boundary layer flow over small-amplitude rigid wavy terrain. Of specific interest is the instability of the flow to spanwise-periodic initially exponentially growing longitudinal vortex modes via the Craik–Leibovich CL2-O(1) instability mechanism and whether it is this instability mechanism that gives rise to longitudinal vortices evident in the recent experiments of Gong et al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 17 publications
4
47
0
Order By: Relevance
“…This result is consistent with the stability analysis performed by Phillips et al . [] who showed that the Craig‐Lebovich CL2 instability can develop on the mean turbulent profile in the absence of turbulent fluctuations. This means that the streaks are induced by large‐scale eddies whose formation is triggered by the roughness elements.…”
Section: Channel Flow Over 2‐d Sinusoidal Symmetric Dunessupporting
confidence: 94%
“…This result is consistent with the stability analysis performed by Phillips et al . [] who showed that the Craig‐Lebovich CL2 instability can develop on the mean turbulent profile in the absence of turbulent fluctuations. This means that the streaks are induced by large‐scale eddies whose formation is triggered by the roughness elements.…”
Section: Channel Flow Over 2‐d Sinusoidal Symmetric Dunessupporting
confidence: 94%
“…Comparisons with experiments by Gong, Taylor & Dörnbrack (1996) further indicate that CLg is physically realizable (Phillips, Wu & Lumley 1996). But unlike CL2, where instability is assured in a neutral wavy disturbance only when differential drift and shear are of the same sense (for temporal wavy disturbances see Phillips 2002Phillips , 2003, instability to CLg must satisfy the necessary but not sufficient Craik-Phillips-Shen criterion (Craik 1982;Phillips & Shen 1996).…”
Section: Introductionmentioning
confidence: 93%
“…For example, the condition for Taylor-Görtler instability -sufficient concave curvature of near-wall streamlines -is locally satisfied above y + ∼ 50 (Brown & Thomas 1977). Alternatively, Phillips, Wu & Lumley (1996) consider a Craik-Leibovich (type 2) instability mechanism, involving x-dependent perturbation growth on shear flows with small-amplitude streamwise undulation. In particular, they present evidence of Craik-Leibovich-based longitudinal vortex formation near a (rigid) wavy wall, suggested to be locally representative as well of the fluctuating streamwise velocity field in near-wall turbulence.…”
Section: Centrifugal and Wave-shear Instabilitiesmentioning
confidence: 99%